IDAE framework: A guide for establishing industry-driven academic programs - Challiz De Lima Omorog (Institute of Advanced Engineering and Science, 2020)
An empirical study using descriptive-quantitative methods was conducted to investigate this hypothesis and examine the appropriateness of the framework components on the potential offering of an academic program at Camarines Sur Polytechnic Colleges (CSPC). The Identify, Determine, Assess and Establish (IDAE) model provided strategies and results essential for institutional decision-making. The model also proposes that if at least one of the components- I-D-A were not satisfied, the last component- E should not be pursued. Simply put, the academic program should not be instituted. However, further research is encouraged to support these arguments.